Hands-On Time in Simulation-Based Ultrasound Training – A Dose-Related Response Study - Mahmood, Oria; Jørgensen, Rikke Jeong; Nielsen, Kristina Rue; Konge, Lars; Russell, Lene (Ultrasound International Open, 2022)
Purpose Point of care ultrasound (POCUS) is widely used, but the sensitivity and specificity of the findings are highly user-dependent. There are many different approaches to ultrasound training. The aim of this study was to explore the effects of hands-on practice when learning POCUS.Methods Junior doctors with no or limited ultrasound experience were included in the study and divided into three groups. They all completed a Focused Assessment with Sonography for Trauma (FAST) course with different amounts of hands-on practice: 40 minutes (n=67), 60 minutes (n=12), and 90 minutes of hands-on time (n=27). By the end of the course, they all completed a previously validated test.Results More hands-on time improved the mean test scores and decreased the test time. The scores of the 40-, 60-, and 90-minute groups were 11.6 (SD 2.1), 12.8 (SD 2.5), and 13.7 (SD 2.5), respectively (p<0.001). The 90-minute group completed the test significantly faster than the other two groups (20 versus 26 minutes, p=0.003). A large inter-individual variation was seen.Conclusion The necessary amount of hands-on training is unknown. This study demonstrates that performance increases with prolonged hands-on time but the inter-individual variation among trainees is very large, thereby making it impossible to define the “optimal” time. This supports the use of the concept of mastery learning where each individual trainee can continue training until proficiency is reached.
Keywords: METHODS & TECHNIQUES; ultrasound; THEMES; education; AREAS; STRUCTURES & SYSTEMS; medical